Pesantren and Environmental-based Educational Innovation: Building Environmentally Friendly Pesantren - Yusuf, M. (Lembaga Pengembangan Pesantren dan Diniyah Provinsi Jawa Timur, 2024)
This study explores the application of environmental-based educational innovation in Islamic boarding schools (pesantren) to build environmentally friendly pesantren. The main focus of this study is the involvement of pesantren in environmental conservation, which is still limited even though Islamic teachings firmly support the values ​​of ecological sustainability. This study uses a qualitative literature study method to analyze literature related to Islamic boarding schools, environmental education, and sustainability strategies in the context of Islamic educational institutions. The main findings reveal that pesantren have significant potential to become agents of change in environmentally-based education. Several pesantren have begun implementing environmentally friendly programs, but various challenges must be faced, including limited resources, infrastructure, and resistance to innovation. This study has essential value because it provides a model of educational innovation that integrates Islamic teachings with sustainability principles and is relevant to increasingly pressing global environmental challenges. Thus, this study strengthens the environmentally friendly Islamic education paradigm, which aligns with international efforts to address climate change.